“Immune Gate” of Psychopathology—The Role of Gut Derived Immune Activation in Major Psychiatric Disorders - Rudzki, Leszek; Szulc, Agata (Frontiers in Psychiatry, 2018)
Interaction between the gastrointestinal tract (GI) and brain functions has recently become a topic of growing interest in psychiatric research. These multidirectional interactions take place in the so-called gut-brain axis or more precisely, the microbiota-gut-brain axis. The GI tract is the largest immune organ in the human body and is also the largest surface of contact with the external environment. Its functions and permeability are highly influenced by psychological stress, which are often a precipitating factor in the first episode, reoccurrence and/or deterioration of symptoms of psychiatric disorders. In recent literature there is growing evidence that increased intestinal permeability with subsequent immune activation has a major role in the pathophysiology of various psychiatric disorders. Numerous parameters measured in this context seem to be aftermaths of those mechanisms, yet at the same time they may be contributing factors for immune mediated psychopathology. For example, immune activation related to gut-derived bacterial lipopolysaccharides (LPS) or various food antigens and exorphins were reported in major depression, schizophrenia, bipolar disorder, alcoholism and autism. In this review the authors will summarise the evidence and roles of such parameters and their assessment in major psychiatric disorders.